Relationship between Endothelial Tissue Factor and Thrombogenesis under Blood Flow Conditions - Diquélou, Armelle; Dupouy, Dominique; Gaspin, Dominique; Constans, Jacques; Sié, Pierre; Boneu, Bernard; Sakariassen, Kjell S; Cadroy, Yves (Thrombosis and Haemostasis, 1995)
We have evaluated the relationship between the level of tissue factor (TF) expression by stimulated endothelial cells and thrombus formation under blood flow conditions. Cultures of human umbilical venous endothelial cells (HUVECs) were treated in order to express different levels of TF activity. They were stimulated for 4 h with either I) lipopolysaccharides (LPS, 10 µg/ml), II) recombinant interleukin Iß (IL1ß, 50 Ul/ml) or III) simultaneously with LPS and IL1ß (LPS + IL1ß). TF activity was low on confluent HUVECs or on the corresponding extracellular-matrix (ECM prepared by exposure of HUVECs to 0.1 N NH4OH). In contrast, it was high when HUVECs were stimulated with LPS or IL1ß, and significantly higher (p <0.05) with LPS+IL1ß. The TF activity associated with the stimulated ECM was 2-fold higher (p <0.05) than that expressed on the luminal surface of the stimulated HUVECs, irrespective of the agonist or combination of agonists used.These surfaces were exposed to non-anticoagulated human blood at a venous (50 s-1) and an arterial (650 s-1) wall shear rate in parallel-plate perfusion chambers for 5 min. Thrombus formation was morphologically quantified by measuring the deposition of platelets and fibrin. Fibrin deposition was also immunologically quantified. Fibrin deposition was related to the level of TF expression. Non-stimulated HUVECs and corresponding ECMs were not thrombogenic. The luminal surface of HUVECs stimulated with LPS or IL1ß alone expressed low levels of TF activity and was a poor inducer of platelet deposition and fibrin deposition (<15%) at 50 s-1. In contrast, fibrin deposition increased to 80% when the cells were stimulated with LPS and IL1ß simultaneously. This fibrin deposition was comparable to that found on the corresponding ECM, despite a two-fold lower TF activity. However, at 650 s-1, platelet and fibrin deposition on HUVECs stimulated with LPS + IL1ß were significantly lower than that observed on the corresponding ECM. In all circumstances, the thrombogenicity was TF-dependent, since fibrin deposition was totally blocked by anti-TF antibodies. Thus, it appears that the level of TF activity expressed on endothelial cells governs thrombus formation. However, the impact of TF expression on thrombus formation is also affected by the blood flow.